A call for better data for surveillance and evaluation of caesarean sections in Europe - A joint statement by Euro-Peristat and European Board and College of Obstetrics and Gynaecology (EBCOG) - Velebil, Petr; Durox, Melanie; Zeitlin, Jennifer; Mahmood, Tahir; Euro-Peristat Research Group (European journal of obstetrics, gynecology, and reproductive biology, 2025)
International comparisons highlight differences in healthcare practices, raising questions about the application of evidence-based care when wide variations exist between countries with similar populations and income levels. Caesarean section (CS) rates show significant variation, with national and regional averages differing widely. As a common surgical procedure, this variation affects a large number of people and may have major consequences for maternal and newborn health. Comparable health indicators are essential to analyse CS rates and understand the reasons for this variability. A review of data on CS rates in Europe in international databases, such as those maintained by Eurostat, OECD and WHO, confirmed wide variation in CS rates in Europe, from 16% to over 50%, but showed very limited data available to understand these differences. In contrast, many European countries collect a wide array of data in national health information systems which can be used to investigate variations in CS, including on the timing and indication of the CS, and key population and health system characteristics that affect risks of CS. Based on the published literature, work in the Euro-Peristat network and within the EBCOG advisory board, we propose a list of data items that should be available at the national and international levels to allow comprehensive international surveillance and evaluation of CS practices.
Keywords: Data collection; International comparisons; Cesarean Section; lidé; Female; Europe; Caesarean section (CS); Evropa; Pregnancy; Euro-Peristat; Robson Classification; těhotenství; Variations in CS rates; ženské pohlaví; císařský řez; Humans